Desulphurisation of Mae Moh low-rank coal using ultrasonic waves and microwave irradiation treatment processes with mixture of hydrogen peroxide and hydrochloric acid / Wan Izhan Nawawi Wan Ismail - Wan Ismail, Wan Izhan Nawawi (2007)
Mixture of 6% hydrogen peroxide and O.IN hydrochloric acid (3:7 volume mixed ratio of peroxide to acid) was used to desulphurise Mae Moh low-rank high sulphur coal in the presence of three different processes i.e. ultrasonic waves, microwave irradiation and conventional magnetically stirring processes. The parameters that were used to investigate the effect of sulphur and ash removal from the coal using the three different processes were leaching time (i.e. 0.25, 0.5, 1, 2, 4 and 8 hour for both ultrasonic waves and magnetically stirring processes, and 0.5, 1, 2, 4, 10 and 20 minutes for microwave irradiation process), leaching temperature (30, 50 and 70°C; for both ultrasonic wave and magnetically stirring), and irradiation power (150, 700 and 100 watts for microwave irradiation). The success of the three different processes toward the total sulphur removal was measured by comparing the S/C atomic ratios of the treated coal with the untreated coal. The percent of inorganic sulphur removal in the treated coal was determined by using ASTM D2492, with organic sulphur being determined by the difference. In general, the treatments of coal sample using three different processes led to ca. 35-68, 29-93, 43-100, 2-50% and 37-71% of total sulphur, pyrite, sulphate, organic and ash removal, respectively. The optimal temperature and time for desulphurisation using ultrasonic waves were at 50°C and 0.5 hour, respectively, and for the magnetically stirring process were at 50°C and 0.5 - 8 hour, respectively. The optimal power and time for the microwave irradiation process, however, was at 700 watt and 4 minute, respectively. By comparing the three different processes, the ultrasonic waves treatment at 50°C for 0.5 hour was found to be the optimum condition for sulphur and ash removal with approximately 65, 82, 83, 48 and 55% of total sulphur, pyrite, sulphate, organic and ash reduction were achieved, respectively, without affecting the coal heating value. Moreover, pyrolysis on the treated coal samples via thermogravimetry analysis showed a slight increase in reactivity with comparison to the untreated coal sample. The by-product of coal desulphurisation contained humin compound and can be used in fertilizer industry. Further, the calorific values of treated coal samples were comparable to the untreated 'coal indicating no significant alteration in the coal macro-structure.